Study on Magnetohydrodynamic flow past two circular cylinders in staggered arrangement - Kamarul Baharin, Nur Marissa; Sapardi, Mohd Azan Mohammed; Ab Razak, Nur Nadhirah; Abdul Hamid, Ahmad Hussein; Syed Abu Bakar, Syed Noh (Penerbit Akademia Baru, 2021)
The fusion reactor is anticipated to be a new source of clean energy. Magnetohydrodynamic flow in the fusion blanket is expected to cause the flow to be highly stable, causing the heat transfer to be poor. Passive vortex promoter such as bluff body is one of the methods found to be has a great potential in optimizing the heat transfer. In this study, two circular cylinders in a staggered arrangement are introduced to promote vortices to enhance heat convection from a heated wall using an electrically conducting fluid under a constant magnetic field. The effect of the Hartmann friction parameter and the height differential onto the Nusselt number were examined. Modified Navier—Stokes equations known as SM82 were used using OpenFOAM to simulate the confined, quasi-two-dimensional, incompressible and laminar MHD flow past the bluff bodies. It was found that the heat transfer is better when the height differential is small.